2008
DOI: 10.1093/mutage/gem052
|View full text |Cite
|
Sign up to set email alerts
|

Using the alkaline comet assay in prognostic tests for male infertility and assisted reproductive technology outcomes

Abstract: Infertility affects one in six couples in Europe during their reproductive years with dysfunctional sperm being one of the most common causes. Conventional semen analysis has proven variable and lacking in prognostic value so, over the past decade, more useful molecular fertility biomarkers have been explored. Among the tests showing most promise are those measuring sperm DNA quality. Sperm DNA damage has been closely associated with numerous indicators of reproductive health, including, fertilization, embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 116 publications
0
50
0
5
Order By: Relevance
“…Analysis of sperm DNA fragmentation Currently, three major tests of sperm DNA fragmentation are most frequently used, including the Comet assay (single-cell gel electrophoresis), [45][46][47] the terminal deoxynucleotidyl transferase-mediated dUDP nick end-labeling (TUNEL) assay 48 and the SCSA. 9,11 Comet, TUNEL and SCSA all label single-or double-stranded DNA breaks; however, unfortunately, most of the available techniques for detection of sperm DNA damage provide limited information on the nature of the DNA lesions detected and none of them enable us to depict the exact etiology and pathogenesis of impairment of sperm DNA.…”
Section: -44mentioning
confidence: 99%
“…Analysis of sperm DNA fragmentation Currently, three major tests of sperm DNA fragmentation are most frequently used, including the Comet assay (single-cell gel electrophoresis), [45][46][47] the terminal deoxynucleotidyl transferase-mediated dUDP nick end-labeling (TUNEL) assay 48 and the SCSA. 9,11 Comet, TUNEL and SCSA all label single-or double-stranded DNA breaks; however, unfortunately, most of the available techniques for detection of sperm DNA damage provide limited information on the nature of the DNA lesions detected and none of them enable us to depict the exact etiology and pathogenesis of impairment of sperm DNA.…”
Section: -44mentioning
confidence: 99%
“…Their application has shown that sperm DNA (and chromatin) damage can be associated with reduced rates of fertilization in vivo, by natural and assisted conception (Spano et al 2000, Bungum et al 2007. Their predictive value for spontaneous abortions, malformations, developmental defects, or chromosomal damage in offspring is under active investigation (Lewis & Agbaje 2008, Sakkas & Alvarez 2010. These tests have been demonstrated to be also useful in epidemiology studies aimed at investigating the reproductive impact of environmental or occupational compounds and in experimental toxicology trials to evaluate the reprotoxicity of physical-chemical noxiae (Evenson & Wixon 2005, Bennetts et al 2008, Perry 2008, Delbès et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used is the Sperm Chromatin Structure assay (SCSA), the single-cell gel electrophoresis assay (COMET assay) in its alkaline, neutral, 2-tailed versions (Singh et al, 1997;Lewis and Agbaje, 2008;Enciso et al, 2009), the terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay (Gorczyka et al, 1993) and the sperm chromatin dispersion (SCD) test (Fernandez et al, 2003). Although these tests correlate to each other (Aravindan et al 1997;Zini et al 2001;Perera et al 2002;Erenpreiss et al 2004, Donelly et al, 2000 and all measure single and double strand breaks, the methodologies are based on different principles and different aspects of sperm DNA damage (Makhlouf and Niederberger, 2006).…”
Section: Sperm Dna Integrity Testingmentioning
confidence: 99%
“…One example of this is DNA breaks (Evenson et al, 2002;Sharma et al, 2004;Lewis and Aitken, 2005;Lewis 2007;Aitken, 2006;Erenpreiss et al, 2006a;Evenson and Wixon, 2006;Muratori et al, 2006;Collins et al, 2008;Lewis and Agbaje, 2008;Lewis et al, 2008;Bungum et al, 2007;Zini and Sigman, 2009;Aitken and De Iuliis, 2010;.…”
Section: Introductionmentioning
confidence: 99%